Decreased autophagy impairs decidualization of human endometrial stromal cells: a role for ATG proteins in endometrial physiology - Citrinovitz, Ana Cecilia Mestre; Strowitzki, Thomas; Germeyer, Ariane (International journal of molecular sciences, 2019)
During the menstrual cycle, the endometrium undergoes cyclic changes of cellular proliferation, differentiation, and death, an essential preparation of the endometrium for its interaction with the implanting embryo. In particular, the differentiation of endometrial stromal cells, named decidualization, ensures the formation of a proper feto-maternal interface for a regulated trophoblast invasion and correct placental orientation and growth. Interestingly, autophagy, an intracellular degradation process of great importance for the maintenance of cellular homeostasis, plays an important role in cell proliferation, differentiation, and growth. In the endometrium, increased detection of autophagy markers correlates with the progression of the menstrual cycle. However, until now, it was unknown whether autophagy contributes to the proper function of the endometrium. In this study, we show that autophagy is increased during in vitro decidualization of human endometrial stromal cells. Furthermore, we demonstrate that the knockdowns of two important autophagy-related (ATG) proteins, ATG7 and ATG5, impaired decidualization, confirming a positive role of these proteins and of autophagy for the correct decidualization of human endometrial stromal cells. In conclusion, in this work, we describe a previously unknown functional connection between autophagy and endometrial physiology.